Temperature, dietary lipids, and Aeromonas hydrophila modulate self-protection mechanisms in pacu Piaractus mesopotamicus Holmberg 1887 - de Faria, Camila de Fátima Pereira [UNESP]; Gonçalez, Fábio Lopes [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Wiley, 2025)
Water temperature has a direct influence on several physiological processes in fish. This study investigated the effects of the exposure of pacu (Piaractus mesopotamicus) to 10 days of reduced temperature in stress and innate immune and antioxidant systems, all of which are involved in energy mobilization. Two groups of fish, fed a control diet or a diet with a higher lipid level, were exposed for 10 days to 16°C and then inoculated with Aeromonas hydrophila bacterin. Samples were taken before and after 5 and 10 days of exposure. The results showed that the low temperature (16°C) was a stressor, increasing cortisol levels. Higher levels of cortisol were seen in fish with more body fat, especially at 16°C, compared to those fed control diet. The immune system was enhanced by low temperature that activated the hemolytic activity of the complement system (HAC50) and lysozyme after 10 days of exposure in fish with more body fat. Bacterin inoculation, regardless of temperature and body fat, impaired the respiratory activity of leukocytes, but the complement system activity remained at the levels seen before cold activation. Similarly, lysozyme remained at the levels seen before cold activation, showing later activation. Furthermore, soon after inoculation (at 3 and 6 h), bacterin induced oxidative stress that decreased at 24 h when the concentration of reduced glutathione (GSH) showed lower levels, suggesting that GSH was consumed to attenuate the oxidative stress. Pacu was resilient to the reduced temperature, displaying protective responses to the stressful condition using lipids to modulate these responses.
Keywords: antioxidant system; cold shock; cortisol; innate immunity; oxidative stress